2013
DOI: 10.1007/s10865-013-9524-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Routine Health Behaviors Following Late-life Bereavement: A Systematic Review

Abstract: This systematic review examines the relationship between late-life spousal bereavement and changes in routine health behaviors. We review six behavioral domains/modifiable risk factors that are important for maintaining health among elderly populations: physical activity, nutrition, sleep quality, alcohol consumption, tobacco use, and body weight status. Thirty-four articles were identified, derived from 32 studies. We found strong evidence for a relationship between bereavement and nutritional risk and involu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 65 publications
(151 reference statements)
7
58
1
1
Order By: Relevance
“…Caregivers' severe depressive‐symptom prevalence decreased significantly after 13 months of bereavement, consistent with reports that acute grief reactions to the death of a beloved generally resolve within 6 to 12 months . In addition, bereaved caregivers' mental health‐related QOL improved significantly throughout the first 2 bereavement years, whereas their physical health‐related QOL remained steady, despite abundant evidence that losing a beloved can create numerous somatic health problems for bereaved caregivers . Our results suggest that bereaved caregivers can move on after their loss, especially considering that their severe depressive‐symptom prevalence was significantly lower after 3 months postloss than when they were caregiving (Table ).…”
Section: Discussionsupporting
confidence: 87%
“…Caregivers' severe depressive‐symptom prevalence decreased significantly after 13 months of bereavement, consistent with reports that acute grief reactions to the death of a beloved generally resolve within 6 to 12 months . In addition, bereaved caregivers' mental health‐related QOL improved significantly throughout the first 2 bereavement years, whereas their physical health‐related QOL remained steady, despite abundant evidence that losing a beloved can create numerous somatic health problems for bereaved caregivers . Our results suggest that bereaved caregivers can move on after their loss, especially considering that their severe depressive‐symptom prevalence was significantly lower after 3 months postloss than when they were caregiving (Table ).…”
Section: Discussionsupporting
confidence: 87%
“…The present study found that residents’ physical activity and functional independence were influenced by a number of factors, as did earlier studies: ageism (Swift, Abrams, Lamont, & Drury, ), social capital (Lees et al, ) and loss of a loved one (Stahl & Schulz, ), illness or pain (Schutzer & Graves, ) and staff support (Henwood, Neville, Baguley, & Beattie, ). Chen () found that past sedentary lifestyle was one barrier to physical activity in residential aged care.…”
Section: Discussionsupporting
confidence: 85%
“…This gap between abilities and demands, which can vary among individuals given their unique situations and contexts, justifies tailored intervention strategies that improve skills such as mastering tasks of daily living, engaging in self-care behaviors, and functioning socially as a single or uncoupled person in society (Caserta et al, 2004; Stahl & Schulz, 2014; Utz, 2006). Thus, an individually-delivered intervention is particularly relevant for those whose spouse/partner died after a terminal illness like cancer because they may be better helped by an approach that is tailored to their specific needs (Bergman & Haley, 2009; Burton, Zdaniuk, Schulz, Jackson, & Hirsch, 2003; Caserta et al, 2013; Patterson & Dorfman, 2002; Penson, Green, Chabner, & Lynch, 2002).…”
Section: Partners In Hospice Care (Phc): the Emergence Of An Individumentioning
confidence: 99%